Cryogenic treatment of an AISI D2 steel: The role of isothermal martensite formation and "martensite conditioning". (September 2020) - Villa, Matteo; Somers, Marcel A.J.
Highlights: Martensite formation in AISI D2 steel at cryogenic temperature is time dependent. Martensite formation proceeds at a maximum rate at approximately −110 °C. Martensite formation at cryogenic temperature is associated with magnetic softening. Abstract: Vibrating sample magnetometry, VSM, was applied to follow the evolution of the austenite-to-martensite transformation in AISI D2 tool steel at cryogenic temperatures and to determine the associated changes in magnetic hardness. Data shows that the transformation can progress during cooling from room temperature (RT) to −193 °C and, more surprising, during re-heating from −193 °C to RT, indicating the formation of, so called, isothermal or thermally activated martensite. The thermally activated conversion of austenite into martensite occurred in the temperature range −33 °C ≤ T ≤ −173 °C and was fastest at −113 °C. Additionally, VSM revealed that the magnetic hardness decreases in correspondence with the formation of martensite. Data is interpreted in terms of continuous growth of the (ferromagnetic) martensite units at cryogenic temperatures that reduces the number of (paramagnetic) austenite regions retained in the material. Eventually, the work is put in perspective to arrive at an understanding of the effect of cryogenic treatment on the microstructure and performance of martensitic steels.